Miescher’s cheilitis: A case report with literature review (Journal of Pathology of Nepal, 2018)
Miescher’s cheilitis is an inflammatory disorder characterized by chronic lip swelling due to granulomatous inflammation. It is rare disorder first described by Miescher in 1945. It is monosymptomatic form of Melkersson-Rosenthal syndrome. We report a case of Miescher’s cheilitis in a 59-year old lady presented with recurrent swelling and erythema of upper lip and submental area with no features of facial palsy and fissuring of tongue. Laboratory tests including serum complement C3, C4 and C1 esterase inhibitor functional were within normal limits. The biopsy from the upper lip revealed dermal edema, dilated lymphatic channels and multiple granulomas. After exclusion of other causes of orofacial granulomatosis, the diagnosis of Miescher’s cheilitis was made. Patient was treated with oral hydroxychloroquine and topical tacrolimus and mometasone cream with gradual improvement.